Kinerja Mekanistik Campuran Beraspal dengan Mensubstitusi Agregat Kasar dengan Batu Vulkanik Merah - Agus Ariawan; D.M. Priyantha Wedagama; I Nyoman Arya Thanaya; I Gusti Agung Ratih Kusuma Wardani; I Putu Chandra Wibawa (Jurnal Teknik Sipil, 2023)
Abstract The increasingly limited availability of volcanic stone in nature has caused road pavement construction materials to use black volcanic stone mixed with red volcanic stone, which is lighter in density and porous. This research aims to analyze the mechanistic performance of asphalt mixtures by substituting coarse aggregate with red volcanic stone up to a percentage of 10% at a granule size of ½", 3/8", No. 4 according to conditions in the field. The asphalt mixture is made using the marshall method. Mechanistic characteristics are obtained from indirect tensile stiffness modulus (ITSM) testing according to BS EN 12697-26: 2012, dynamic creep testing (BS EN 12697–25:2005) and indirect tensile fatigue testing (ITFT) according to BS EN 12697–24:2012 using a dynapave universal testing material (UTM) 30 test tool. The marshall characteristic values of the asphalt mixture meet the specifications of the Ministry of PUPR (2020), the stiffness characteristic increases by an average of 6.9 % for each additional substitution of 5% red volcanic stone. Deformation resistance increases with typical values of creep slope, concluding that asphalt mixtures can be used for heavy traffic loads (ESA >106). The fatigue resistance characteristics are lower (earlier to collapse) compared to without red volcanic stone substitution and there is a decrease in fatigue resistance of 2.18% for each additional 5% red volcanic stone substitution. Keywords: Mechanistic performance, asphalt mixture, substitution, red volcanic stone